2020
DOI: 10.48550/arxiv.2006.15708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Null and Force-Free Electromagnetic Field

Govind Menon

Abstract: In this paper we describe the electrodynamics of a null and force-free field in completely geometric terms. As was previously established in [1], solutions to force-free electrodynamics are governed by the existence of certain special types of foliations of spacetime. Here we prescribe the nature of the foliations in a coordinate free formalism in the null case. Finally, we illustrate all of our general results by constructing a null, force-free electrodynamic field in an Friedmann-Lemaitre-Robertson-Walker (F… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The original derivation of the class of solutions presented here can be found in [16]. In [20] we showed that null foliations of spacetime admitting an equipartition of null mean curvature allows for a class of null force-free solutions. However, in the non-null case this is not true.…”
Section: Illustrative Examplesmentioning
confidence: 84%
See 4 more Smart Citations
“…The original derivation of the class of solutions presented here can be found in [16]. In [20] we showed that null foliations of spacetime admitting an equipartition of null mean curvature allows for a class of null force-free solutions. However, in the non-null case this is not true.…”
Section: Illustrative Examplesmentioning
confidence: 84%
“…It was also clear that null and non-null solutions to FFE belonged to two very different categories of foliations. In [20], the theory of null and force-free fields and its connection to foliations of spacetime was formulated in a geometric and covariant manner. This works, then, completes the task of recasting the remaining non-null FFE and its correspondence with foliations in a covariant formalism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations